2007
DOI: 10.1291/hypres.30.1059
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obesity and Chronic Kidney Disease in Japanese: Differences in Gender and Hypertensive Status?

Abstract: Obesity is a known risk factor for hypertension and diabetes, both of which ultimately promote renal dysfunction. In the current study, we investigated the association between body mass index (BMI) and chronic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
4
24
2
1
Order By: Relevance
“…To date, there are no reports on the effects of the combination of MetS and CKD on CVD occurrence. The influence of CKD on CVD incidence can reportedly be greater in men than in women (Ishizaka et al, 2007). A number of reports suggest that MetS, defined by NCEP-ATPIII criteria, as in our study, may influence the incidence of CVD, coronary heart disease in particular, in men relative to women (Qiao, 2006).…”
Section: Discussionsupporting
confidence: 49%
“…To date, there are no reports on the effects of the combination of MetS and CKD on CVD occurrence. The influence of CKD on CVD incidence can reportedly be greater in men than in women (Ishizaka et al, 2007). A number of reports suggest that MetS, defined by NCEP-ATPIII criteria, as in our study, may influence the incidence of CVD, coronary heart disease in particular, in men relative to women (Qiao, 2006).…”
Section: Discussionsupporting
confidence: 49%
“…This study showed a Several previous studies have shown that increased BMI is a risk factor for development of CKD. In a community-based cross-sectional study in Japan, Ishizaka et al found that increased BMI was associated with low eGFR only in men (13). The OR for developing new-onset kidney disease, defined as a GFR of less than 59.3 mL/min/1.73 m 2 in women and less than 64.3 mL/min/1.73 m 2 in men, was 23% (OR, 1.23; 95% CI, 1.08-1.41) for one SD increase in BMI (14).…”
Section: Discussionmentioning
confidence: 99%
“…The greater risk associated with male gender may be partly due to sex-related differences in the prevalence of hypertension (4,5) and/or dyslipidemia (6). Although the level of significance was not given, in a study of 8,168 Japanese subjects undergoing general health screening, the mean levels of systolic blood pressure (SBP), diastolic blood pressure (DBP), low density lipoprotein (LDL), cholesterol, and triglyceride (TG) were all higher in men (n= 5,244) than in women (n= 2,924) (7). In that study, mean high density lipoprotein (HDL) cholesterol levels were lower in men than in women.…”
Section: Introductionmentioning
confidence: 99%